A Real-World Nationwide Study on COVID-19 Trend in Italy during the Autumn–Winter Season of 2020 (before Mass Vaccination) and 2021 (after Mass Vaccination) Integrated with a Retrospective Analysis of the Mortality Burden per Year - Luca Roncati; Carlo Galeazzi; Giulia Bartolacelli; Stefania Caramaschi (Microorganisms, 2024)
SARS-CoV-2 virulence is known to increase with lowering of environmental temperature and solar ultraviolet radiation; therefore, we have focused our real-world nationwide study concerning with COVID-19 trend and dynamics on the coldest seasons of the year in Italy, the Western country hardest hit at the onset of the pandemic, comparing the autumn–winter of 2020 (before mass vaccination but when the emergency machinery was fully operative in terms of tracing and swabs) with the autumn–winter of 2021 (after mass vaccination), and analyzing the mortality burden by age groups and life stages in the years 2019 (pre-COVID-19), 2020 (before mass vaccination), and 2021 (after mass vaccination). Methods: During the state of national health emergency, the Civil Defense Department released the aggregate data coming from the Higher Institute of Health, the Ministry of Health, the Italian Regions, and the Independent Provinces, to inform the population about the pandemic situation, daily. Among these data, there were the number of contagions, performed swabs, hospitalizations in Intensive Care Units (ICU), non-ICU patients, and deaths. By means of a team effort, we have collected and elaborated all these data, comparing the COVID-19 pandemic in Italy during the autumn–winter of 2020 with the autumn–winter of 2021. Moreover, we have extracted from the database of the National Institute of Statistics the total number of annual deaths in Italy during the years 2019, 2020, and 2021, comparing them to each other in order to evaluate the mortality burden attributable to COVID-19. Results: From the autumn–winter of 2020 to the autumn–winter of 2021, the contagions increased by ≈285%, against a ≈290% increase in the performed swabs; therefore, the mean positivity rate passed from 8.74% before mass vaccination to 8.59% after mass vaccination. The unprecedent vaccination campaign allowed a ≈251% abatement in COVID-19 deaths, and a reduction of ≈224% and ≈228% in daily ICU and non-ICU hospitalizations due to COVID-19, respectively. Regarding COVID-19 deaths, in 2020, there was a mortality excess of ≈14.3% quantifiable in 105,900 more deaths compared to 2019, the pre-COVID-19 year; 103,183 out of 105,900 deaths occurred in older adults (≥60 years), which is equivalent to ≈97.4%, while in adults over 50, the segment of population just below older adults, in 2020, there were 2807 more deaths than in 2019. Surprisingly, from the analysis of our data, it is emerged that in people under the age of 40 in the years 2019, 2020, and 2021, there were 7103, 6808, and 7165 deaths, respectively. This means that in subjects under 40 during 2020, there were 295 fewer deaths than in 2019, while during 2021, there were 357 more deaths than in 2020, equivalent to ≈5.2% more. Conclusions: COVID-19 is a potential life-threatening disease mainly in older adults, as they are the most vulnerable due to inherent immunosenescence and inflammaging. Extensive vaccination in this segment of population with up-to-date vaccines is the means to reduce deaths, hospitalizations, and ICU pressure in the public interest. In the event of future threats, a new mass vaccination campaign should not be implemented without taking into account the individual age; it should primarily be aimed at people over 60 and at patients of any age with immune deficits, and secondly at people over 50. COVID-19 vaccination shows a favorable benefit–risk ratio in older adults, while the balance steps down under the age of 40; this younger segment of the population should be therefore exempt from any mandatory vaccination.